2003
DOI: 10.1002/rcm.909
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biotransformation of 17α‐methyltestosterone in the horse revisited: identification of 17‐hydroxymethyl metabolites in equine urine by capillary gas chromatography/mass spectrometry

Abstract: The in vivo phase I biotransformation of 17 alpha-methyltestosterone in the horse leads to the formation of a complex mixture of regio- and stereoisomeric C(20)O(2), C(20)O(3) and C(20)O(4) metabolites, excreted in urine as glucuronide and sulphate phase II conjugates. The major pathways of in vivo metabolism are the reduction of the A-ring (di- and tetrahydro), epimerisation at C-17 and oxidations mainly at C-6 and C-16. Some phase I metabolites have been identified previously by positive ion electron ionisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…It represented less than 0.2% of the total excretion for this steroid. In addition, this epimerization has also been found in the horse (Dumasia, 2003). Abundances observed in the spectrum of A4 are in agreement with those reported for 17-epimethyltestosterone (Schänzer et al, 1992).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It represented less than 0.2% of the total excretion for this steroid. In addition, this epimerization has also been found in the horse (Dumasia, 2003). Abundances observed in the spectrum of A4 are in agreement with those reported for 17-epimethyltestosterone (Schänzer et al, 1992).…”
Section: Resultssupporting
confidence: 89%
“…Two main metabolites were identified in the metabolism of 17␣-methyltestosterone in human: 17␣-methyl-5␣-androstane-3␣,17␤-diol (A2) and 17␣-methyl-5␤-androstane-3␣,17␤-diol (A3) (Schänzer and Donike, 1993). Hydroxylated metabolites have been described in several animals including the horse (Dumasia, 2003;McKinney et al, 2007;Yamada et al, 2007) and the heifer (Blokland et al, 2005).In doping control analysis, the detection of steroid metabolites is normally performed by gas chromatography-mass spectrometry (GC-MS) after trimethylsilylation (Schänzer and Donike, 1993;Ayotte et al, 1996;Saugy et al, 2000), achieving the required sensitivity of 2 ng/ml (WADA Technical Document TD2004MRPL version 1.0, 2007, http://www.wada-ama.org/rtecontent/document/perf_limits_2. pdf).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that structurally related MTS and MSL yield metabolites in common in human [1,2]. There are also reports of the urinary metabolites of MTS in horse; Stanley et al [3] and Dumasia [4] used GC/MS to identify 17-hydroxymethyl metabolites, and McKinney et al examined the stereochemistry of urinary metabolites by comparing with authentic reference standards [5]. The main steps in the metabolism of MTS in horses are as follows: reduction of A-ring 3-oxo and 4-ene groups; oxidation at C-6, C-15, and C-16; and epimerization at C-17 during phase I biotransformation, followed by sulfate and glucuronide conjugation during phase II biotransformation [3,4].…”
Section: Introductionmentioning
confidence: 97%
“…There was little information on the biotransformation of oral anabolic steroids in horses, although this class of steroids is known as potential drugs of abuse in human sports due to their ease of administration and normally shorter excretion times. It was not until the late 1990s that racing chemists started to direct more eff ort to studies of these substances, including ethylestrenol (Kim et al, 1996), oxymetholone and mestanolone (Tang et al, 2000), danazol (Tang et al, 2001), methandrostenolone (McKinney et al, 2001a), norethandrolone (McKinney et al, 2001b), normethandrone (Fox et al, 2001), 17a-methyltestosterone (Dumasia, 2003), 1-testosterone (Kwok et al, 2004), clostebol acetate and mesterolone , 7-keto-dehydroepiandrosterone acetate , methenolone acetate and turinabol (Ho et al, 2007).…”
Section: Introductionmentioning
confidence: 98%